A Phase I Study to Evaluate the Safety, Tolerability, Pharmacokinetics of BGT-002, a Novel ATP-Citrate Lyase Inhibitor, in Healthy Chinese Subjects - Liu Y; Yu C; Zhang Y; Xie Z; Wang Y; Qian H; Liang L; Liu Y; Chen Q; Jia J; Yan S; Lai X; et al. (Drug Design, Development and Therapy)
Yun Liu,1,2,* Chengyin Yu,1– 3,* Yifan Zhang,3 Zhifu Xie,3 Yating Wang,1,2 Hongjie Qian,1,2 Liyu Liang,1,2 Yanmei Liu,1,2 Qian Chen,1,2 Jingying Jia,1,2 Sai Yan,4 Xiaoyin Lai,4 Wei Li,4 Jingya Li,3 Yangming Zhang,4 Fajun Nan,3 Chen Yu1,2 1Shanghai Xuhui Central Hospital/Zhongshan-Xuhui Hospital, Fudan University, Shanghai, People’s Republic of China; 2Phase I Clinical Research and Quality Consistency Evaluation for Drugs, Shanghai Engineering Research Center, Shanghai, People’s Republic of China; 3State Key Laboratory of Drug Research, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai, People’s Republic of China; 4Burgeon Therapeutics Co., Ltd., Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fajun Nan; Chen Yu, Email fjnan@simm.ac.cn; cyu@shxh-centerlab.comObjective: This Phase I study evaluated the safety, tolerability, pharmacokinetics (PK) and pharmacodynamics (PD) of BGT-002, a novel ATP-citrate lyase (ACLY) inhibitor, in healthy Chinese adults.Methods: This study included three parts: Part I (single-ascending-dose study), Part II (multiple-ascending-dose study), and Part III (food effect study). A total of 104 healthy subjects were enrolled in the study and were given BGT-002 tablet or placebo per protocol requirements. Blood samples were collected for pharmacokinetic and pharmacodynamic analysis. Safety was assessed by clinical examinations and adverse events.Results: In Part I, BGT-002 demonstrated rapid absorption with a Tmax of 0.67 to 1.75 hours, and slow elimination with a T1/2 of 24.53 to 72.86 hours, prolonged with increased dosages. Cmax and AUC0-∞ ranged from 1.55 to 48.39 μg/mL, and 31.09 to 2930.69 h·μg/mL, respectively. In Part II, the accumulation index (Rac) of Cmax and AUCtau following 14 days of consecutive administration were 3.53 to 3.62 and 5.29 to 5.59, respectively, with a dose-proportionality PK profile. The levels of total cholesterol (TC), non-high-density lipoprotein cholesterol (non-HDL-C), and low-density lipoprotein cholesterol (LDL-C) were maximally decreased by 15.80%, 18.50%, and 22.37%, respectively. In Part III, the geometric mean ratio (90% CI) of fed to fasting condition in Cmax and AUC0-∞ of BGT-002 were 73.11% and 98.36%, respectively, indicating a minor food effect on the absorption rate. Across the study, two cases of Grade 3 adverse events (elevated blood triglycerides) were reported, both of which were assessed as not related to BGT-002. No serious adverse events were observed.Conclusion: BGT-002 demonstrated favorable safety, tolerability, and lipid-lowering effects, supporting its potential for further clinical development.Clinical Trial Registration: ChiCTR2200057793(https://www.chictr.org.cn/showproj.html?proj=160210); ChiCTR2300067474(https://www.chictr.org.cn/showproj.html?proj=182183); ChiCTR2300067472(https://www.chictr.org.cn/showproj.html?proj=184079).Keywords: safety, tolerability, pharmacokinetics, pharmacodynamics, BGT-002, novel ACLY inhibitor